2021
DOI: 10.1186/s12875-021-01574-x
|View full text |Cite
|
Sign up to set email alerts
|

Context and general practitioner decision-making - a scoping review of contextual influence on antibiotic prescribing

Abstract: Background How contextual factors may influence GP decisions in real life practice is poorly understood. The authors have undertaken a scoping review of antibiotic prescribing in primary care, with a focus on the interaction between context and GP decision-making, and what it means for the decisions made. Method The authors searched Medline, Embase and Cinahl databases for English language articles published between 1946 and 2019, focusing on gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Perhaps this is due to prescribers treating patients based on severity of illness, and concern that bacterial infection may underlie the symptoms. This theory is compatible with the multitude of contextual factors that influence antibiotic prescribing [ 32 ]. As a sensitivity analysis, shifting index date later did result in a slight decline in postdiagnosis prescribing in the community cohort, though still substantially elevated from baseline.…”
Section: Discussionmentioning
confidence: 57%
“…Perhaps this is due to prescribers treating patients based on severity of illness, and concern that bacterial infection may underlie the symptoms. This theory is compatible with the multitude of contextual factors that influence antibiotic prescribing [ 32 ]. As a sensitivity analysis, shifting index date later did result in a slight decline in postdiagnosis prescribing in the community cohort, though still substantially elevated from baseline.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have shown that the most common reason for non-disclosure of DS use is that healthcare personnel do not ask [ 4 , 14 ]. GPs’ practice style affects patients [ 31 ] and clinical decision making varies between medical doctors even in comparable situations [ 21 , 32 ]. This includes medical tasks that are not done, such as not obtaining sufficient anamnestic information and sufficient medical examinations as shown in another study [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially when the likelihood of risk is unknown, lack of knowledge promotes pessimistic appraisals of risk as well as avoidance of decision-making [ 35 , 36 ]. Uncertainty is known to affect medical practice [ 21 ]. One problem in dealing with this uncertainty, may be the lack of communication between GPs regarding DS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roope et al 10 concluded that revising antibiotic guidelines to be less prescriptive about duration and making duration conditional on patient factors and treatment response could help safely increase the frequency of early discontinuation of antibiotics in hospitals. Al-Azzawi et al 11 highlight the need for context to be taken into account in theories of medical decision-making, which would impact education, clinical practice and policymaking. However, there is no universally accepted definition of context in medical terms.…”
Section: Introductionmentioning
confidence: 99%